THE IMPACT OF INTRINSIC MOTIVATION, ORGANIZATIONAL CULTURE AND JOB SATISFATION ON EMPLOYEE PERFORMANCE AT HUMAN CAPITAL SERVICES GROUP (PT BANK MANDIRI) - Reza, Muhamad; Elmi, Farida (Dinasti International Journal of Digital Business Management, 2022)
The decrease in employee performance would derive in business results are being less than optimal is the beginning of a phenomenon which occurs in a company. This research has purpose to determine the impact of intrinsic motivation, organizational culture and job satisfaction towards employee performance at Human Capital Services Group (PT Bank Mandiri). The data analysis through multiple linear regression analysis. This type of research is included in quantitative. The sample subjects in this research were 65 employees of Human Capital Services Group (PT Bank Mandiri). The results from this multiple linear regression analysis partially indicate if the intrinsic motivation, organizational culture and job satisfaction had a significant impact on employee performance at Human Capital Services Group.